Associations between binge drinking frequency and tobacco use among young adults. (September 2016) - Gubner, Noah R.; Delucchi, Kevin L.; Ramo, Danielle E.
Abstract: Tobacco use is greater among young adults who binge drink; yet there is limited research on tobacco use characteristics among different types of binge drinkers based on frequency. We aimed to characterize this relationship among young adults (18–25 years old) who used both substances in the past month (smoked ≥ 1 cigarette, and drank ≥ 1 alcoholic beverage) using an anonymous online survey. Participants (N = 1405, 65.0% male) were grouped based on binge drinking frequency and compared for tobacco use characteristics and demographics using bivariate analyses and multinomial logistic regression. Binge drinking frequency groups were: non-binge drinkers who consumed alcohol (0 days; 27.5%); occasional (1–3 days; 37.9%); intermediate (4–8 days; 21.9%); and frequent (9 + days; 12.7%) binge drinkers. Comparing each binge drinking group to non-binge drinkers: Both occasional and frequent binge drinkers smoked more cigarettes per day (p = 0.001; p = 0.002); frequent binge drinkers reported greater temptations to smoke in positive affective/social situations (p = 0.02); intermediate binge drinkers were less likely to have a tobacco abstinence goal (p = 0.03) but more likely to have made a serious tobacco quit attempt; all of the binge groups were more likely to be social smokers (all p < 0.01). Overall, we also found a high rate of smoking on binge drinking days. Individuals smoked cigarettes on 85.7% ± 32.9% of days they binge drank. Extent of binge drinking (not just prevalence) is an important factor influencing smoking characteristics in young adults. Highlights: We examined smoking characteristics across binge drinking groups in young adults. Self-identifying as a social smoker was associated with any binge drinking. Other tobacco use characteristics differed by frequency of binge drinking High rate of smoking while binge drinking regardless of frequency (85.7% ± 32.9%)